COMBINED EFFECTS OF RIBAVIRIN AND DIAZINON ON HEPATIC, PANCREATIC AND KIDNEY BIOMARKERS IN FEMALE ALBINO RATS - H. A. AbdElmonem; M .M Abbas; A. H. Mahmoud (Journal of Animal and Plant Sciences, 2016)
The interaction between chemicals such as drugs and pesticides within ecological system is a complex one as it occurs among environment, host and chemicals. The present study was conducted to evaluate the combined effects of ribavirin at 30 mg/kg bw and 1/10LD50 of diazinon, at 30mg/kg bw, on liver, pancreas and kidney functions of female albino rats. Twenty four female albino rats were equally divided into four groups and were orally given 0.5 ml corn oil (served as a control), ribavirin, diazinon and ribavirin plus diazinon for 5 consecutive days/week up to 4 weeks. The results revealed that ribavirin alone produced no significant differences in serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), total, direct and indirect bilirubins, albumin (Alb.), A/G ratio, α-feto protein (AFP), amylase, lipase, insulin, urea, calcium (Ca) and inorganic phosphorus (P) compared to the control group. However, there was significant increase in alkaline phosphatase (ALP), uric acid, creatinine, potassium (K) and sodium (Na), whereas, final body weights, total proteins (TP) and globulins (Glob.) were significantly decreased compared to the control groups. The  results  also showed that  treatment  with diazinon induced significant increases in the activities of ALP, AST, ALT,  levels of total, direct and indirect bilirubins, AFP, amylase, urea, uric acid, creatinine, K and Na. However, significant decrease in final body weights, TPs, Alb, and Globs were observed compared to the control groups. In conclusion, ribavirin had a efficacy in ameliorating the liver impairment and pancreatic inflammation induced by diazinon, on the contrary this antiviral drug caused additional burden on the kidney leading to more deterioration in the renal function.
Keywords: Diazinon; Ribavirin; Biochemical parameters; Female rats